Disability "In-Justice": The Benefits and Challenges of "Yarning" With Young People Undergoing Diagnostic Assessment for Fetal Alcohol Spectrum Disorder in a Youth Detention Center. (January 2020) - Hamilton, Sharynne; Reibel, Tracy; Maslen, Sarah; Watkins, Rochelle; Jacinta, Freeman; Passmore, Hayley; Mutch, Raewyn; O'Donnell, Melissa; Braithwaite, Valerie; Bower, Carol
Undertaking research with young people presents an array of methodological challenges. We report the findings from a qualitative study that took place alongside a fetal alcohol spectrum disorder (FASD) prevalence study among detainees in Australia. Of 38 participants, 27 were Aboriginal youth. Interviews were conducted using "social yarning" and "research topic yarning, " an Indigenous research method which allows for data collection in an exploratory, culturally safe way. A complex interplay emerged between social yarning and research topic yarning which provided a space to explore responsively with participants their experiences of FASD assessments. Flexibility, including language adaptation and visual descriptions about assessments, was utilized to assist participants recall and retell their experiences. There were, however, challenges in gathering data on the assessment experiences of some participants. We describe how employing a "yarning" method for collecting data could benefit children and young people undergoing neurodevelopmental assessments in the future.